FAKTOR – FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN BERAT BAYI LAHIR RENDAH DI RSUD DR. IBNU SUTOWO BATURAJA TAHUN 2017 - Yustina Oktarida; Yeviza Puspita Sari (STIKES Abdurrahman. Pusat Informasi dan Manajemen, 2017)
The research goal is to know the dactors assoiated with the incidence of LBW in Baturaja Ibnu Sutowo Baturaja hospital in 2017 – 2018. The research method using analytical survey method with cross sectional approach, the entire population in this study are listed in the birth room Ibnu Sutowo Baturaja period mart – july 2017 amonted 399 total study. Based on the result of statistics test of 399 respondent, be foud that as many as 144 respondent (40.9 %) have on incident of low birth weight, the result of Chi Square analysis velated between the birth spacing has get p value = 0,00, and the relation of education variable has get p value : 0,001, and there is have the meaning relation between the birth spacing, work, and education with the incedents of low birth weigh at Dr. Ibnu Sutowo Ragional Publish Hospitall of Baturaja in 2017. Sugessted for officer of health, education and research intitusion to conduct counseling’s to raise awarenessand increase knowladrge and public knowladge about weight birth low make the result of this study as a reference for subsequent and research. Tujuan penelitian adalah diketahuinya faktor – faktor yang berhubungan dengan kejadian BBLR di RSUD Dr. Ibnu Sutowo Baturaja tahun 2017. Dari hasil uji statistik dari 399 responden kejadian berat badan lahir rendah sebanyak 144 responden ( 40,9 % ) dan yang tidak mengalami kejadian Berat Badan Lahir Rendah sebanyak 255 responden ( 63,9% ). Hasil analisa Chi-square berhubungan antara variabel jarak kelahiran di dapat nilai p value = 0.00 dan hubungan variabel pendidikan didapatkan p value = 0,001 dan hubungan variabel pekerjaan p value = 0,001. Dan ada hubungan yang bermakna antara jarak kelahiran, pekerjaan, pendidikan dengan kejadian BBLR di RSUD Dr. Ibnu Sutowo Baturaja tahun 2017. Disarankan bagi petugas kesehatan, Instansi pendidikan, dan peneliti agar mengadakan penyuluhan, guna meningkatkan kesadaran dan menambah wawasan tentang Berat Badan Lahir Rendah serta menjadi referensi untuk pendidikan dan penelitan berikutnya.